Consumer's Attitude Toward Private Label and Its Relationship with Their Motivational Values - Nasution, Reza Ashari; Dewi, Amanda Permata; Sembada, Agung Yoga (SBM ITB, 2009)
Private label penetration is increasing from time to time. Past research have highlighted individual customer demographic characteristics that relate to private label purchase. Those research, however, have neglected the role of personal values in driving consumer behavior. This research is aimed to fill this gap by studying private label purchase behavior in a university in Bandung, Indonesia and its relation to the personal values of the respondents. Schwartz Value System is applied after comparing this with other value systems. Two dimensions in the system, which are opennes to change and conservation are analyzed in relation with private label purchase behavior of students in the university. The dimensions are selected because of their direct intuitive link with private label purchase. Using correlation analysis, the research provides an important finding about the role of personal values (in terms of opennes to change vs conservation) in private label purchase.Keywords: private label, personal value, Schwartz Value Systems, Bandung, Indonesia, openness toÂ change, conservation, purchase behavior, consumer behavio